Contrasting habitat use of diurnal and nocturnal fish assemblages in temperateWestern Australia - Harvey, Euan; Butler, J.; McLean, D.; Shand, J. (Elsevier, 2012)
This study examined the diversity and relative abundance of fish species in six coastal habitats during the day and at night. Habitats included seagrass beds, Ecklonia macroalgal beds, other macrophytes, deep reef, rhodolith beds and sand. Surveys were conducted using baited remote underwater stereo-video systems, which at night were equipped with either white or red lights. Three research questions were examined;1) do fish assemblages sampled during the day differ to those sampled at night across six inshore and near shore marine habitats? 2) Are patterns of habitat associations displayed by diurnal fishes maintained at night? 3) Do stereo-BRUVs sample different fish assemblages when equipped with red versus white lights? Diurnal surveys sampled significantly greater species richness (66% greater) and numbers of individuals (92% more than red lights, 82% than white lights) than nocturnal surveys. Diurnal surveys also showed greater discrimination in the fish assemblages between the six habitats with replicate samples from a habitat clustered together.This clustering of replicate samples was reduced at night where a number of species of fish were seen in multiple habitats. Thirty-one percent of the species viewed at night were seen on multiple habitats, but only a single habitat during the day.Compared to red lights, white lights surveyed a greater number of individuals and species in rhodolith beds (94% more individuals and 63% more species) and over sand (94% more individuals, 83% more species). This was likely due to an attraction of fish to bait fish accumulating near the white light source, but not in the red light source. However, surveys of fish assemblages at night were deemed most effective when red lights wereused, because this lighting type had an improved ability to statistically distinguish fish assemblages across the habitats surveyed. By conducting nocturnal survey studies researchers may obtain a more holistic understanding of habitat use by fish species and account for this usage in biodiversity and fisheries management plans.